Detection of Group B Streptococcus (GBS) from Antenatal Screening, Maternal GBS Colonization and Incidence of Early-Onset Neonatal Disease (GBS-EOD): A National Survey, December 2022 to February 2023, Italy - Michela Sabbatucci; Pierangelo Clerici; Roberta Creti (Microorganisms)
Invasive neonatal GBS infections constitute a major cause of sepsis and meningitis in Western countries. Vaginal/rectal GBS colonization during pregnancy is the main risk factor for the development of early-onset infections (GBS-EOD) in newborn by vertical transmission at birth, in addition to prematurity and stillbirth. In Italy, intrapartum antibiotic prophylaxis (IAP) to prevent GBS-EOD is offered to pregnant women who tested as GBS-positive in late pregnancy. Passive surveillance in Italy showed that a non-negligible number of GBS-EOD cases (about 50%) occurred from GBS-negative pregnant women. This finding prompted the launch of a national online survey from 15 December 2022 to 12 February 2023 to investigate the microbiological procedures followed for GBS identification in Italian public and private microbiology laboratories, the prevalence of maternal GBS colonization, and the incidence of GBS-EOD cases. The survey results demonstrated that national guidelines for the prevention of EOD-GBS cases as well as harmonization of microbiological methodologies for GBS identification in the antenatal screening are needed.